The influence of bait on remote underwater video observations in shallow-water coastal environments associated with the North-Eastern Atlantic - Robyn E. Jones; Ross A. Griffin; Stephanie R. Januchowski-Hartley; Richard K.F. Unsworth (PeerJ, 2020)
The use of baited remote underwater video (BRUV) for examining and monitoring marine biodiversity in temperate marine environments is rapidly growing, however many aspects of their effectiveness relies on assumptions based on studies from the Southern Hemisphere. The addition of bait to underwater camera systems acts as a stimulus for attracting individuals towards the camera field of view, however knowledge of the effectiveness of different bait types in northern temperate climbs is limited, particularly in dynamic coastal environments. Studies in the Southern Hemisphere indicate that oily baits are most effective whilst bait volume and weight do not impact BRUV effectiveness to any great degree. The present study assesses the influence of four bait types (mackerel, squid, crab and no bait (control)) on the relative abundance, taxonomic diversity and faunal assemblage composition at two independent locations within the North-Eastern Atlantic region; Swansea Bay, UK and Ria Formosa Lagoon, Portugal. Two different bait quantities (50 g and 350 g) were further trialled in Swansea Bay. Overall, patterns showed that baited deployments recorded statistically higher values of relative abundance and taxonomic diversity when compared to un-baited deployments in Swansea Bay but not in Ria Formosa Lagoon. No statistical evidence singled out one bait type as best performing for attracting higher abundances and taxonomic diversity in both locations. Faunal assemblage composition was however found to differ with bait type in Swansea Bay, with mackerel and squid attracting higher abundances of scavenging species compared to the crab and control treatments. With the exception of squid, bait quantity had minimal influence on bait attractiveness. It is recommended for consistency that a minimum of 50 g of cheap, oily fish such as mackerel is used as bait for BRUV deployments in shallow dynamic coastal environments in the North-Eastern Atlantic Region.